2012
DOI: 10.1007/s11746-012-2085-z
|View full text |Cite
|
Sign up to set email alerts
|

Bubble and Crystal Formation in Lipid Systems During High‐Intensity Insonation

Abstract: The objective of the present research was to monitor bubble and crystal formation in lipids during highintensity insonation. High-intensity ultrasound was generated with a 20-kHz probe. Bubble and crystal formations were recorded using a low-intensity ultrasound spectrometer operating at 1 MHz central frequency. Bubble formation was monitored in soybean oil (SBO) during insonation for different time periods (5, 10 and 60 s) and at different temperatures (22, 24, 26, 28, and 30°C). Ultrasound attenuation due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The PLE system has been shown to produce a complex environment where hot spots 11,12 , bubbles, bubble clusters [13][14][15] , inertial 16,17 cavitation and non-inertial [18][19][20] cavitation exist and where different processes may be driven (for example surface erosion 21,22 , chemical changes [23][24][25][26][27] and mass transfer [28][29][30] effects). While many experimental studies of these effects in water environments exist, oils, and in particular lipids 31 have received little fundamental investigation. Hence, it is timely, particularly considering the technological significance of this material, to characterise and contrast the cavitation fields that are generated in these liquid materials as reported here.…”
Section: Introductionmentioning
confidence: 99%
“…The PLE system has been shown to produce a complex environment where hot spots 11,12 , bubbles, bubble clusters [13][14][15] , inertial 16,17 cavitation and non-inertial [18][19][20] cavitation exist and where different processes may be driven (for example surface erosion 21,22 , chemical changes [23][24][25][26][27] and mass transfer [28][29][30] effects). While many experimental studies of these effects in water environments exist, oils, and in particular lipids 31 have received little fundamental investigation. Hence, it is timely, particularly considering the technological significance of this material, to characterise and contrast the cavitation fields that are generated in these liquid materials as reported here.…”
Section: Introductionmentioning
confidence: 99%
“…
Dear Sir,Power ultrasound (PU) has been recently used to induce the crystallization of several edible lipids [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In general, results from these studies show that PU induces the formation of smaller crystals, promotes the formation of a stable polymorphic form, decreases the induction time of crystallization, and generates harder and more elastic materials.
…”
mentioning
confidence: 99%
“…The presence of bubbles after sonication ceased was also shown in reflection measurements. These results showed that the number of bubbles in the media after the sonication ceased depends on the duration of sonication and on sample temperature (Martini et al 2012).…”
Section: Resultsmentioning
confidence: 85%
“…Acoustic techniques have the advantage that they can be used with opaque materials and that they can be used to detect bubbles that oscillate at small amplitudes (Leighton 1994). Martini et al (2012) has recently studied the formation and life cycle of bubbles generated during sonication in an edible lipid (soybean oil) using low intensity ultrasound. The experimental conditions and results obtained will be discussed below.…”
Section: Bubble Formation In Lipid Samplesmentioning
confidence: 99%
See 1 more Smart Citation